Shades of Becoming Toward Regenerative Futures: Revelatory Purposes and Process in Sustainability Education and Public Pedagogy - King , Jordan (Journal of Public Pedagogies, 2022)
The daunting complexities of the apocalyptic present compel new pedagogies for learning, action, and change toward regenerative futures. This paper explores how areas of convergence and emergence between public pedagogy and sustainability education reveal purposes and processes that enable individual and collective experiences of regeneration. Specifically, the paper considers how features of sustainability education, realms of sustainability change, and forms of public pedagogy can be linked to elements of regeneration. The paper presents a theoretical framework that leverages the metaphor of different shades of becoming to capture the experience of regeneration through a dynamic and iterative process of un-becoming, re-becoming, and becoming. Ultimately, the paper suggests implications for how public pedagogy negotiates apocalyptic challenges, orients both pedagogies and publics toward sustainability, and navigates possibilities to enable regenerative futures.